Thermal Shock Resistance of Epoxy Reinforced Fiber Betel Nut Against the Strength of Bending and Impact Energy - Hendriwan Fahmi (Jurnal Teknik Mesin (JTM), 2018)
The development of material engineering technology is now beginning to experience an increase in the utilization of natural fibers as a reinforcement in composites. The purpose of this research is to know the effect of thermal shock on bending strength and impact matrix of epoxy with betel fiber. In this study used betel fiber with a length of 1cm and epoxy resin matrix. Matrix and reinforcement composition 30%: 70% v, pinewood was soaked with 30% NaOH for 30 minutes. The composite was heated at a temperature of 1000C for 1 hour, then dipped into water with a variation of 10.15,20 cycles. Bending and impact testing based on ASTM 790 and ASTM D-265. The results showed that the highest bending strength was obtained at the thermal shock of 10 cycles of 76.75 N / mm2 and the lowest at 20 cycles of 48.26 N / mm2. At impact test at get biggest impact energy obtained at thermal shock 10 cycle that is 0,756 J and the smallest at 20 cycle that is equal to 0,060 J. This result show that bigger cycle at thermal shock hence composite strength will decrease.